A Drosophila model of Parkinson's disease. - Feany, M.B.; Bender, W.W. (Nature, 2000)
Parkinson's disease is a common neurodegenerative syndrome characterized by loss of dopaminergic neurons in the substantia nigra, formation of filamentous intraneuronal inclusions (Lewy bodies) and an extrapyramidal movement disorder. Mutations in the alpha-synuclein gene are linked to familial Parkinson's disease and alpha-synuclein accumulates in Lewy bodies and Lewy neurites. Here we express normal and mutant forms of alpha-synuclein in Drosophila and produce adult-onset loss of dopaminergic neurons, filamentous intraneuronal inclusions containing alpha-synuclein and locomotor dysfunction. Our Drosophila model thus recapitulates the essential features of the human disorder, and makes possible a powerful genetic approach to Parkinson's disease.